2009
DOI: 10.1002/ijc.24437
|View full text |Cite
|
Sign up to set email alerts
|

ING2 is upregulated in colon cancer and increases invasion by enhanced MMP13 expression

Abstract: Inhibitor of growth 2 (ING2) is associated with chromatin remodeling and regulation of gene expression by binding to a methylated histone H3K4 residue and recruiting HDAC complexes to the region. The aim of our study is to investigate the regulation of ING2 expression and the clinical significance of upregulated ING2 in colon cancer. Here, we show that the ING2 mRNA level in colon cancer tissue increased to more than twice than that in normal mucosa in the 45% of colorectal cancer cases that we examined. A put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 62 publications
(108 reference statements)
4
59
0
Order By: Relevance
“…Furthermore, in IHC results we investigated if the ING2 expression was translocated from nucleus to cytoplasm in several NSCLC tissues, especially in ING2 high staining samples, in contrast to normal tissues. In agreement with our results, the aberrantly localization of ING2 was also reported in some other tumors, including HCC [35] and colon cancer [22]. Moreover, study on ING1 and ING3, homologs of ING2, also found similar event in brain tumor [36] and HCC [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, in IHC results we investigated if the ING2 expression was translocated from nucleus to cytoplasm in several NSCLC tissues, especially in ING2 high staining samples, in contrast to normal tissues. In agreement with our results, the aberrantly localization of ING2 was also reported in some other tumors, including HCC [35] and colon cancer [22]. Moreover, study on ING1 and ING3, homologs of ING2, also found similar event in brain tumor [36] and HCC [37].…”
Section: Discussionsupporting
confidence: 91%
“…Another report by Saito M provides an animal model to study idiopathic and iatrogenic infertility in men found the function of ING2 in spermatogenesis and also demonstrated an evidence of ING2 as a tumor suppressor by increased incidence of soft-tissue sarcomas in Ing2-/-mice [33]. Interestingly, a research on colon cancer suggest ING2 also play roles as a tumor oncogene, which demonstrated ING2 was upregulated and increased invasion by enhanced MMP-13 [22]. In addition, a putative NF-κB binding site was found in the promoter of ING2 and the activation of NF-κB could positively regulate ING2 expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Decrease of nuclear ING2 protein was observed in melanoma [57]. On the other hand increased expression of ING2 mRNA was shown in colon cancer [97]. We recently demonstrated that frequent deletion of ING2 locus at 4q35.1 associated with advanced tumor stage in HNSCC [98].…”
Section: Disorders Of Ing Family Genes In Human Tumorsmentioning
confidence: 93%
“…Decrease of nuclear ING2 protein was observed in melanoma [50]. On the other hand increased expression of ING2 mRNA was shown in colon cancer [51]. Moreover, ING2 may play a role in melanoma initiation, since reduction of nuclear ING2 has been reported in radial as well as vertical growth phases in metastatic melanoma as compared to dysplastic nevi [52].…”
mentioning
confidence: 97%